2022
DOI: 10.3390/su14159766
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Source and Biofertilizer Influence K Release and Fruit Yield of Mango (Mangifera indica L.): A Three-Year Field Study in Sandy Soils

Abstract: Arid degraded soils have a coarse texture and poor organic matter content, which reduces the activity of microorganisms and soil enzymes, and thus the soil quality, plant yield and quality decrease. Potassium solubilizing bacteria (KSB) have been suggested to increase the activity of soil enzymes and increase the release of potassium from natural K-feldspar in the arid degraded soil, and thus potentially reduce the rates of the application of chemical fertilizers. Field studies were conducted for three success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Amended soil with PG and/or PM greatly improves plant growth by increasing nutrient availability. Similar results were reported by 53 , 54 , who reported that organic amendments improved the soil quality.…”
Section: Discussionsupporting
confidence: 90%
“…Amended soil with PG and/or PM greatly improves plant growth by increasing nutrient availability. Similar results were reported by 53 , 54 , who reported that organic amendments improved the soil quality.…”
Section: Discussionsupporting
confidence: 90%
“…The essential nutrients (N, P, and K) promote an increase in biomass yield by improving root growth, activating cellular enzymes, ameliorating photosynthesis, conserving energy, and positively affecting other fundamental processes in the plant body. Potassium sources can influence the K + release and fruit yield of M. indica ( Wang et al., 2022 ). It emphasizes the importance of potassium uptake and transport system from root to leaves and fruit.…”
Section: Discussionmentioning
confidence: 99%
“…The application of appropriate K + fertilizer to mango trees increases fruit yield and value. Nevertheless, unconstrained fertilizer usage can result in financial loss to farmers, and excessive use of non-renewable resources is raising concerns about large-scale sustainable development ( Bahadur et al., 2019 ; Wang et al., 2022 ). Foliar application of K + is also practiced to improve fruit yield.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, VC is regarded a nutrient-dense biofertilizer with a diversi ed microbial community (13)(14). VC contains nutrients that are readily taken up by the plants, such as, available-P, K, Ca and Mg. VC is an excellent soil amendment or conditioner because of high porosity, aeration, drainage, waterholding capacity and microbial activity [15]. Vermicomposting and composting are two distinct processes, and it is crucial not to confuse the two [16].…”
Section: Introductionmentioning
confidence: 99%